let a=b

a^2=ab

a^2-b^2=ab-b^2

(a+b)(a-b)=b(a-b)

a+b=b

2b=b

2=1

This series of equations is given to prove that 2=1.Although this may appear correct there is a fallacy in this.At step 5 both sides have been divided by a-b.But a=b.So a-b=o.An d, no number can be divided by 0.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewesti found a solution when we compare 1=2 with a=b => a is not equal to b thats it any doubts reply me ill say

Log in to reply

I had given the solution that it is incorrect.Then how can you give a solution for a incorrect questionLog in to reply

that's what iam saying a is not = b you considered a wrong equation in the beggening

Log in to reply

How can you tell that \(a \neq b\).I had provided the word let a=b.If a=b in the above series of equation, we get 1=2Log in to reply

We had that too in a quiz after we discussed trigonometric ratios :D The questions was "Prove that 2=1" I kept going to 1=0 until we were given a hint - difference of two squares :D

Log in to reply